Penerapan Teori Revolusi Sosiokultural Dalam Pembelajaran SKI Menurut Perspektif Lev Vygotsky - Erlina Ralista; Anggun Navisha; Yunus Habibi; M. Rafly; Bagus Mahardika (Jurnal Ilmu Pendidikan, 2025)
The learning of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) in schools still tends to be informative, teacher-centered, and lacks active student involvement, resulting in underdeveloped historical thinking skills, critical thinking, and students’ socio-cultural awareness. This condition indicates the need for a more contextual and interactive learning approach so that history is not merely understood as a sequence of events, but as a meaningful social process. This study aims to examine the application of Lev Vygotsky’s sociocultural revolution theory in Islamic Cultural History learning and its relevance to students’ cognitive and social development. The research method employed is a literature study by analyzing various scientific sources, including books, articles, and journals that discuss Vygotsky’s sociocultural theory and the practice of Islamic Cultural History learning. The findings indicate that the application of the Zone of Proximal Development (ZPD) concept, scaffolding, social interaction, the use of language, and cultural artifacts can lead to more contextual, collaborative, and dialogical Islamic Cultural History learning. This approach encourages students to actively understand history and relate it to real-life contexts, while also instilling Islamic cultural values and character. Therefore, it can be concluded that Lev Vygotsky’s sociocultural revolution theory is highly relevant for application in Islamic Cultural History learning to enhance students’ critical thinking skills, historical awareness, and overall learning quality.